THE MINIMUM INCOME SCHEME REFORM IN LITHUANIA - Lazutka, Romas (Ekonomika, 2015)
The article reviews the current social assistance scheme in Lithuania and its recent reform. The aim of this paper is to evaluate the scheme in three dimensions: coverage of poor people, adequacy of benefit amounts, and social assistance reconciliation with work incentives. The analysis of the minimum income protection reform is based mainly on the data from Survey of Income and Living Conditions and Administrative Data from the Ministry of Social Security and Labour. The paper discovers the changing role of the minimum income scheme in the context of an economic cycle, its targeting to low-income strata of the population and an adequate amount at least for families with children. However, the growing incentives of local authorities to reallocate funds envisaged for social assistance to other needs can erode the scheme. The article ends with several recommendations to policy makers.